Development of In Vitro Conservation Medium of Carica pubescens Lenne & K. Koch through Nutrients Concentration Reduction and Osmoregulator Addition - Rahayu, Enni Suwarsi; Habibah, Noor Aini; Herlina, Lina (Biosaintifika: Journal of Biology & Biology Education, 2015)
Carica pubescens Lenne & K. Koch is a rare species that need to be conserved. The research aim was to develop a slow growth method of in vitro conservation medium through determining some effects of nutrition decreasing availability in the conservation medium on growth and survival of explants. Establishing epicotyls reached from in vitro seed germination was grown on diluted basic medium of 75% MS (Murashige and Skoog), 50% MS, 25% MS, while osmoregulator compound of mannitol and sorbitol was added to the full MS medium in several concentrations. The treatments were arranged in a completely randomized design with three replications. The epicotyls were grown at storage medium for 12 and 16 weeks, then their survival were evaluated at regeneration medium and rooting medium. The diluted basic medium and osmoregulator addition were evaluated for its influence in retarding the culture growth in terms of improved survival over the period of 16 weeks. Data analyzed by one way analysis of variance and Duncans multiple range test. The results showed that the decreasing of nutrition concentration suppressed the growth of the epicotyls until 16 weeks after conservation. Epicotyls taken from 16 weeks after conservation could grow on the regeneration medium. The best survival was shown by the 75% MS, 50% MS and supplementing of 20 g/l mannitol treatments. Based on these results, 50% MS medium is recommended for storage C. pubescens for 16 weeks with no sub-culture.Carica pubescens Lenne & K. Koch (karika dieng) merupakan tanaman yang langka sehingga perlu dilestarikan. Penelitian ini bertujuan untuk memperoleh medium penyimpanan in vitro dengan teknik pertumbuhan minimal dengan mengamati pengaruh penurunan ketersediaan nutrisi dalam medium terhadap penurunan pertumbuhan dan daya tumbuh eksplan.Eksplan berupa epikotil kecambah in vitro. Perlakuan penurunan ketersediaan nutrisi dilakukan melalui reduksi konsentrasi nutrisi dari medium Murashige & Skoog (MS) dan penambahan osmoregulator (manitol dan sorbitol) dengan berbagai konsentrasi. Penelitian dilakukan dengan rancangan acak lengkap satu faktor dengan tiga ulangan. Epikotil dipelihara dalam medium penyimpanan selama 12 dan 16 minggu, kemudian dievaluasi daya tumbuhnya dengan memelihara dalam medium regenerasi dan medium pengakaran. Data dianalisis dengan analisis varians satu arah dan uji Duncan. Hasil penelitian menunjukkan bahwa penurunan kecepatan penyerapan nutrisi berpengaruh terhadap pertumbuhan eksplan. Epikotil yang telah disimpan selama 12 minggu dan 16 minggu dan ditumbuhkan kembali pada medium regenerasi masih dapat tumbuh dengan intensitas tertinggi pada perlakuan pengenceran 50% MS dan 75% MS, serta penambahan manitol 20 g/l. Komposisi medium ini dapat dimanfaatkan untuk penyimpanan karika dieng selama 16 minggu tanpa sub-kultur. Konsentrasi medium MS 50% direkomendasikan untuk digunakan dalam penyimpanan C. pubescens selama 16 minggu tanpa sub-kultur.